Internet of things in health care: case of cardiovascular diseases in Congo Brazzaville - Cherif, Ali Ouchar; Mankiti Fati, Aristide; Moukala Mpele, Pierre (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In this paper, we present the implementation of a system to prevent cases of cardiovascular disease by allowing patients to have optimal monitoring at a lower cost every day. To achieve this, a system containing a connected cardiogram was designed through telecommunications and digital technology. The results obtained are encouraging insofar as this system facilitates the permanent monitoring of the evolution of heart rhythm in patients. It also enables telemedicine for all doctors, physists and professors in Africa, as the number of specialists is very low. But broadband usage in Africa is about 46%; in Congo Brazzaville, for example, it is 5%, with internet costs very high compared to international offers and the Congolese minimum wage. This work is an important detail to take into account in the development of our work in order to reduce the costs of this digital surveillance as much as possible.